Civic attitudes and the design of labor market institutions: which countries can implement the Danish flexicurity model? - Yann Algan; Pierre Cahuc (Institute for the Study of Labor (IZA), 2006)
We argue that the efficiency of the Danish flexicurity Model, which combines high unemployment benefits with low job protection and high participation rate, relies on strong public-spiritedness. We also argue that Continental and Mediterranean European countries are unlikely to be able to implement the Danish Model because the lack of public-spiritedness of their citizens raises moral hazard issues which hinder the implementation of efficient public unemployment insurance.
Keywords: J23; J65; J68; 330; job protection; unemployment benefits; civic attitudes